A large-scale screening and functional sorting of tumour microenvironment prognostic genes for breast cancer patients - Xiao, Bo; Li, Mingwei; Cui, Mingxuan; Yin, Chengliang; Zhang, Bo (Frontiers in Endocrinology, 2023)
Purpose: To systematically establish a comprehensive tumor microenvironment (TME) related genes and targeting miRNAs network for breast cancer patients. Methods: An innovative prognosic model was generated based on TME related genes (760 genes). The primary TME genes were selected from constructing database and verified in testing database. The internal relationships between the potential TME genes and breast cancer patients prognosis were deeply explored. The associated miRNAs for the TME genes were generated and the functions of each individual primary TME members were examined in breast cancer cell line. Results: Compared with sibling control, the breast cancer patients demonstrated 55 differentially expressed TME genes with 31 were considered as protective genes, while the remaining 24 genes genes were considered as risk genes. According to the lambda values of the LASSO Cox analysis, the potential 15 TME genes were: ENPEP, CCDC102B, FEZ1, NOS2, SCG2, RPLP2, RELB, RGS3, EMP1, PDLIM4, EPHA3, PCDH9, VIM, GFI1 and IRF1. Among these, there was remarkable linear internal relationship for CCDC102B but nonlinear relationships for others with breast cancer patients prognosis. Using siRNA technique, we abolished the expression of TME gene respectively. 7 of the 15 TME genes (NOS2, SCG2, RGS3, EMP1, PDLIM4, PCDH9 and GFI1) were involved in cell proliferation enhancement, cell apoptosis destruction, cell invasion or migration promotion of breast cancer. 6 of them (CCDC102B, RPLP2, RELB, EPHA3, VIM and IRF1) were favorable for maintenance of cell invasion or migration. Only 2 of them (ENPEP and FEZ1) were preferable for the processes of cell proliferation and apoptosis. Conclusion: This integrated study hypothesis an innovative TME-associated genetic functional network for breast cancer patients. The external relationships between these TME genes and the disorder were measured. Meanwhile, the internal molecular mechanisms were also in-depth investigated. All of these shed a light for the future clinical study.